EVALUATION OF THE USE OF ANTIHYPERTENSION DRUG IN HYPERTENSION PATIENTS AT THE GRANDMED LUBUK PAKAM HOSPITAL INSTALLATION IN 2022 - Kartika, Dewi; ., Suprianto; Atika, Nur (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Hypertension is a condition where there is an increase in blood pressure that exceeds the normal limit, namely systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Most women suffer from hypertension because of the hormone estrogen. Patients with hypertension who are not given proper therapy will cause complications that can worsen the condition of hypertension. The higher the prevalence of hypertension sufferers, the use of antihypertensive drugs will increase. This will increase the risk of irrational use of antihypertensive drugs. The purpose of this study was to evaluate the rationality of the use of antihypertensive drugs in the Inpatient Installation of Grandmed Lubuk Pakam Hospital based on the right patient, the right indication, the right drug and the right dose. This research is a type of descriptive research. Data collection was carried out retrospectively by using past data in the form of medical records of hypertension patients for the period January 2021 – February 2022 which met the exclusion and inclusion criteria. The sampling technique used was the purposive sampling technique. The results of this study indicate that the most widely used antihypertensive drugs are combination therapy with Calcium Channel Blokers (CCB) + Angiotensin Converting Enzyme Inhibitors (ACEI) (30,6%); Calcium Channel Blokers (CCB) sebanyak (11%); Calcium Channel Blokers (CCB) + Angiotensin Converting Enzyme Inhibitors (ACEI) + Diuretik sebanyak (11,1%); while the low class of drugs is Calcium Channel Blokers (CCB) + Angiotensin Converting Enzyme Inhibitors (ARB) + Angiotensin Converting Enzyme Inhibitors (ACEI); and diuretics + Angiotensin Converting Enzyme Inhibitors (ACEI) were used (2,8%). The results showed that the rationality of the use of antihypertensive drugs obtained was that the patient was correct 100%, the indication was 100%, the drug was 97,2%, and the dose was 97,2%.